Effect of PEGylated lipid and Lecinol S-10 on physico-chemical properties and encapsulation efficiency of palmitoleate–palmitoleic acid vesicles. (September 2014) - Teo, Yin Yin; Misran, Misni; Low, Kah Hin
Abstract A vesicle is a microscopic particle composed of a lipid bilayer membrane that separates the inner aqueous compartment from the outer aqueous environment. Palmitoleate–palmitoleic acid vesicles were prepared and their physico-chemical properties were investigated. Moreover, mixed vesicles composed of palmitoleic acid and PEGylated lipid and/or a mixture of phospholipids were also prepared. The stabilizing effects of these double-chain lipids on the formation of palmitoleate–palmitoleic acid vesicles were studied. Stability of the vesicle suspension was examined using particle size and zeta potential at 30 °C. The magnitude of the zeta potential was relatively lower in the vesicle suspension with the presence of phospholipid. Although some of the mixed vesicles that were formed were not very stable, they displayed potential for encapsulating the active ingredient calcein and the encapsulation efficiencies of calcein were encouraging. The palmitoleate–palmitoleic acid–DPPE-PEG2000 vesicle showed the most promising stability and encapsulation efficiency.